Relationship Between Physical Activity During COVID-19 Pandemic and Depression Rates in College Students: Analytical Observational Studies among First Year Medical Students at Universitas Diponegoro Semarang - Salafudin Salafudin; Innawati Jusup; Endang Kumaidah; Lusiana Batubara (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: The COVID-19 pandemic has an impact on every individual. Lifestyle changes and reduced physical activity are some of them. Less physical activity will affect a person's psychological problems, one of which is depression. Depression is a common mental disorder with depressed mood, loss of interest or pleasure, decreased energy, feelings of guilt or low self-esteem, sleep or appetite disorders, and reduced concentration. Aim: Determine the relationship of physical activity during the COVID-19 pandemic with the level of depression in first-year students of the Faculty of Medicine, Diponegoro University. Methods: The research design is observational analytics with a cross-sectional approach. The study used the International Physical Activity Questionnaire (IPAQ) and Beck Depression Inventory-II (BDI-II), presented in the google form and disseminated through social media. Respondents filled out one hundred seventy-six questionnaires. The purposive sampling method obtained respondents included in the inclusion and exclusion criteria as many as 114 respondents. The data were tested with the Chi-Square test to assess correlations between variables. Results: We found a significant association between physical activity during the COVID-19 pandemic and depression rates (p=0.043). There is a link between sex and physical activity and depression levels (p=0.007), and there is a significant association between age and physical activity and depression levels during the COVID-19 pandemic (p=0.00).